FUNDRAISING BERBASIS WEBSITE VITAMIN SEA: PROGRAM INOVATIF PENGEKSPLORAN DAN PROMOSI DESTINASI WISATA BAHARI UNTUK MENSUKSESKAN PESONA INDONESIA (WONDERFUL INDONESIA) DALAM MEWUJUDKAN INDONESIA SEBAGAI POROS MARITIM DUNIA - pipin nur azizi; Agung Mahardika (Fakultas Ekonomi dan Bisnis, 2018)
The importance of the tourism role on improving coastal communities welfare and enhance the competitiveness of Indonesian maritime tourism in preparing Indonesia as a world’s maritime axis encourage the writing of this paper. There are many challenges on actualizing tourism sector as the Indonesian economy driver, such as the low quality of human resource and tourism budget. Therefor in this is important how to improve the potential of Indonesian maritime tourism to provide significant benefits to the community and development of Indonesian tourism. The purpose of paper is to provide solution on obtaining donations as a driver of community to create a positive image of Indonesian maritime tourism destination areas as well as open opportunities for the involvement of other sectors in order to improve the society’s welfare. Vitamin Sea is a platform where people can collect and give donation for tourism development. This innovative program also promotes Pesona Indonesia and Wonderful Indonesia program. Based on the results it can be concluded that the implementation of fundraising program based on Vitamin Sea website can help coastal communities in obtaining alternative funding for maritime tourism potential areas and improve the competitiveness of Indonesian maritime tourism.